A decision-making simulator for soccer referees - Samuel, R. D.; Galily, Y.; Guy, O.; Sharoni, E.; Tenenbaum, G. (International Journal of Sports Science & Coaching, 2019)
Decision-making is a critical aspect of soccer referees` performance. Yet current training methods that simulate the refereeing task are limited. Skilled soccer referees (N = 22, M age = 27.14 years, SD = 6.40) were tested on a new decision-making simulator during the active part of the season. They ran on a treadmill for 60 min at varying paces while watching two video sections depicting real matches, in context and in mixed order, and called their match decisions out loud. They completed pre- and post-test assessments of their feelings and perceived exertion, and a post-test assessment of their performance. The referees reported positive feelings prior to and following the test, and rated their performance favourably. They felt the simulator was moderately representative of a real match, and their perceived exertion increased progressively during the test. Decision accuracy levels were higher for simple decisions, such as out of play (73.81%), than for careless fouls (62.86%) or yellow/red cards (25.97%). Decision accuracy levels for yellow/red cards decisions were significantly higher in the in-context section (28.91%) than in the mixed section (20.83%). Decision accuracy levels peaked in the third quarter and decreased during the final quarter. Self-control during the test correlated moderately with overall accuracy. Careless foul decision accuracy was on par with previous studies, supporting the simulator`s validity. The findings support the use of the simulator as a potentially innovative method for training referees in sequential decision-making.